1907 Mont. Laws 260, ch. 107, § 1 - (:unkn) unknown (General Publisher, 1907)
Any person who enters a building belonging to another with intent to commit a felony or other crime by the use of nitro glycerine, dynamite, gun powder or other high explosives or who commits a burglary by the use of such explosives is guilty of burglary with explosives. § 2 Burglary with explosives is punishable by imprisonment in State Prison for not less than fifteen years, and not more than forty years.
--
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME